An Aristotelian Paradigm of Leadership - Kumar Tripathy, Laxman (International Journal of Psychosocial Rehabilitation, 2021)
Leadership in a traditional sense has meant conveying a set of instructions from hierarchical structures (such as management) to others to attain certain goals and objectives. This has been followed in businesses for several years and continues to be followed. In view of new emerging business environments, supported by technological developments and threatened by newer forms of competition, leadership will be searching for other dimensions. This aspect needs a rethink from the perspectives of various stakeholders involved in it. Now it is expected that the leadership must take care of all the stakeholders and fulfill their expectations. So, what exactly does the leadership of the next generation of organizations look like or do? It is attempted to list some of the characteristics. This list of characteristics is just indicative and not exhaustive. Also, it does not mean that the next generation organization would not neccessarily demonstrate these entire characteristics, but it would likely embody some of these traits. Some of them are impact-driven, finance and business-centric, technology and digital savvy, continuous learning, shared leadership, multicultural and culturally competent, consideration of work-life boundaries, social responsibility, and environmental concerns. All these characteristics together result in value addition to the management (board). Thus, apart from paying attention to the routine & regular aspects such as making the organization profitable, managing the competition, and complying with relevant statuary and legal regulations, leadership tomorrow demands some more. It has to be environment-friendly and encompass social empathy. It may give due attention to the needs of underprivileged sections of society and, by suitable means, try to fulfill those needs. This may not be for image building but for keeping the organization active in the real world. The leadership may try to do activities that result in conservation of natural resources by the organization by undertaking suitable activities that are synergic to their business operations and satisfy, to some extent, needs of all their stakeholders. Indeed, tomorrowleadership is challenging, evolving and in the process of ongoing learning in the quest for acquiring new knowledge to maintain its coveted position. Thatnot impossible but certainly a demanding task ahead of all the new and emerging organizations of tomorrow. Objective : The present study compares the Indian and Western Leadership Models & their variables. Research Methodology: Extensive review and analysis of various research papers and articles published over past few years. Resources quoted and borrowed are duly acknowledged. Outcome: An understanding of the variables of Eastern and Western Model of Leadership.